(3GdCHMGK GdeSOOg aj eSGFd eJYOOgs - (3UGdM Hf egOj GdebHdjs ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3bhdg gOi ddeJbjf gd GdeQGO GdeJUfYhf HGdJbhi eYJbOkG Ch eLGRkG Cj ef Yde Gddg efge Pdc s
(3BNQgG (B:s
(3jhe GdaUd heG COQGc eG jhe GdaUd EfJgJ GdeKGd hddg GdMeO hGdefg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdMOjK h GdeUWdMs